Development of an Irrigation Water Quality Database to Identify Water Resources and Assess Microbiological Risks During the Production of Fresh Fruits and Vegetables - Bihn, Elizabeth A.; Mangione, Kurt J.; Lyons, Bill; Wszelaki, Annette L.; Churey, John J.; Stoeckel, Don M.; Worobo, Randy W. (Frontiers in Water, 2021)
An Irrigation Water Quality Database was developed to help assess the microbiological quality of irrigation water used in fruit and vegetable production in 15 counties in New York (NY) State. Water samples from Tennessee (TN) were also included in the database. Four water quality parameters, quantified generic E. coli, specific conductance, pH, and turbidity, were tested. Ground, reservoir, and running water were sampled over two years (2009 and 2010), covering three seasons each year (spring, summer, and fall). TN data are for all three seasons in 2010 only. Overall in NY (254 total samples), ground water had a geometric mean of 1 most probable number (MPN)/100 ml, reservoir water had a geometric mean of 8 MPN/100 ml, and running water had a geometric mean of 52 MPN/100 ml. Overall in TN (63 total samples), ground water had a geometric mean of 1 colony forming unit (CFU)/100 ml, reservoir water had a geometric mean of 5 CFU/100 ml, and running water had a geometric mean of 38 CFU/100 ml. These values are all below the 126 MPN/100 ml United States Environmental Protection Agency’s Ambient Water Quality Standards (AWQS) standard for fresh water. The presence of E. coli had very weak but sometimes statistically signficiant correlatation with water specific conductance, pH, and turbidity, depending on the water source but the r-squared effect was not strong enough to make the other measurements a substitute for testing specifically for E. coli in water.